Existing Practices of Building Information Modeling (BIM) Implementation in the Public Sector - Harun, Aizul Nahar; Samad, Suzana Abd; Mohd Nawi, Mohd Nasrun; Haron, Nuzul Azam (International Journal of Supply Chain Management, 2016)
The Government of Malaysia has taken a proactive action by implementing the strategic ICT-driven or ICT-enabled transformation programmes and ICT plays a critical role in ensuring their efficient and effective implementation. However regardless the efforts, the implementation of BIM in Malaysia mostly on the private sector driven and it is still between BIM level 0 and BIM level 1. As many of countries across the globe have shown great interest and their public sector plays an important role in leading the market towards BIM adoption, the Government of Malaysia and its agencies by capitalising the existing hard and soft-infrastructures in Malaysia should play significant roles to help in stimulate BIM technology in Malaysia to be comparable with other developed countries. This paper through literature review aims to establish a clear understanding about the global BIM implementation in the public sector, to determine the public sector readiness to adopt BIM in Malaysia and to investigate the potential of BIM implementation within the public sector. In addition, suggestions on the focus of the other research papers on BIM implementation within the public sector will be included.